2018
DOI: 10.1002/mds.27391
|View full text |Cite
|
Sign up to set email alerts
|

6‐n‐propylthiouracil taste disruption and TAS2R38 nontasting form in Parkinson's disease

Abstract: Our results show that 6-n-propylthiouracil taster status and TAS2R38 locus are associated with PD. The 6-n-propylthiouracil test may therefore represent a novel, simple way to identify increased vulnerability to PD. Moreover, the presence of the nontasting form of TAS2R38 in PD may further substantiate that disease-associated taste disruption may represent a risk factor associated with the disease. © 2018 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 80 publications
(156 reference statements)
0
35
0
Order By: Relevance
“…Recently, previous studies [49,50] evaluated the role of genetic factors such as odorant-binding protein IIa (OBPIIa) and the 6-n-propylthiouracil (PROP) taster status mediated by the TAS2R38 locus in PD patients. In particular, PROP status is associated with numerous diseases not only correlated to taste function [49], while OBPIIa plays an important effect in the odors perception [50]. "…”
Section: Discussionmentioning
confidence: 99%
“…Recently, previous studies [49,50] evaluated the role of genetic factors such as odorant-binding protein IIa (OBPIIa) and the 6-n-propylthiouracil (PROP) taster status mediated by the TAS2R38 locus in PD patients. In particular, PROP status is associated with numerous diseases not only correlated to taste function [49], while OBPIIa plays an important effect in the odors perception [50]. "…”
Section: Discussionmentioning
confidence: 99%
“…Taste is the body's other major chemosensory system and acts as the final arbiter of food acceptance or rejection behavior (Scott, 2005). Deficits in taste function has also been described in PD (Cossu et al, 2018;Cecchini et al, 2019).…”
Section: Taste Physiologymentioning
confidence: 99%
“…However, this study only investigated taste preferences, showing an increased preference for sucrose (sweet taste) in PD compared to healthy controls. Most of the studies on this topic published afterwards identified a reduced taste sensitivity in PD (ageusia) with an estimated frequency of taste impairment between 9 and 54% (Tarakad and Jankovic, 2017;Cossu et al, 2018;Doty and Hawkes, 2019). Only two groups showed higher sensitivity to taste stimuli in PD compared to controls (Sienkiewicz-Jarosz et al, 2013;Doty et al, 2015).…”
Section: Taste and Pdmentioning
confidence: 99%
“…Hence, it is not surprising that olfactory and taste disorders can have important effects on the quality of life, the importance of which we can realize only when they are lost . Moreover, unexplained smell impairments are acknowledged to be very early biomarkers of the neurodegenerative diseases or mortality, and recently it has been reported that also taste disruption may represent a risk factor associated for these disorders …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Moreover, unexplained smell impairments are acknowledged to be very early biomarkers of the neurodegenerative diseases or mortality, 7 and recently it has been reported that also taste disruption may represent a risk factor associated for these disorders. 8 Taste is the sensory modality that acts as the ultimate checkpoint for food acceptance or rejection. 2 It is generally assumed that the taste system can differentiate the five classic taste qualities (sweet, umami, sour, salty, and bitter), which represent different physiological requirements or pose potential eating hazards, and other additional qualities such as fatty and metallic.…”
Section: Introductionmentioning
confidence: 99%